Challenges Faced by History Teachers in Implementing the Merdeka Curriculum in Vocational Schools - Akmal, Helmi; Abbas, Ersis Warmansyah; Mutiani, Mutiani; Anggriani, Nurul Mila (HISTORIA: Jurnal Program Studi Pendidikan Sejarah, 2026)
This study examines the challenges faced by history teachers in vocational high schools in designing, implementing, and assessing learning activities in alignment with the Merdeka Curriculum framework. The research employs a qualitative descriptive method with data collection techniques, including observation, interviews, and document analysis. The data collected were analyzed using an interactive analysis model. The findings reveal that the primary challenges faced by history teachers in vocational high schools include difficulties in formulating learning outcomes, learning objectives, and the flow of learning objectives. These difficulties hinder teachers' ability to design and develop teaching modules that meet students' needs. Additionally, limited proficiency in using technology and inadequate learning facilities compound the complexities of implementing the Merdeka Curriculum. To address these challenges, school stakeholders must demonstrate a strong commitment to providing specialized training for teachers to enhance their understanding and capabilities in managing learning processes in accordance with the curriculum's principles. Moreover, improvements in learning facilities are essential to support the effective implementation of the curriculum.